Modeling the profitability of commercial banks in Indonesia - Tri Wulandari; Lukytawati Anggraeni; Trias Andati (Economic Journal of Emerging Markets, 2016)
This study examines the effect of lending on Micro, Small and Medium Enterprises (MSMEs) on the profitability of commercial banks in Indonesia. The profitability is measured as Return-on-Assets (ROA) and Return-on-Equity (ROE). It covers the period of 2011 to 2014 using a panel data regression. It finds that MSME loans have a positive impact on ROE. Other internal factors that significantly influence the profitability of banks are MSME’s NPL (non performing loan), the operational efficiency ratio (OER) and loan-to-deposit ratio (LDR), while external factors that significantly influence the profitability of banks are inflation, Gross Domestic Product (GDP) growth and the Bank Indonesia (BI) rate.